2019
DOI: 10.1016/j.jtho.2019.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Landscape and Immune Microenvironment Features of Preinvasive and Early Invasive Lung Adenocarcinoma

Abstract: Background-Understanding the genomic landscape and immune microenvironment features of preinvasive and early invasive lung adenocarcinoma may provide critical insight and facilitate development of novel strategies for early detection and intervention. Methods-A total of 80 tumor tissue samples and 30 paired histologically normal lung tissue samples from 30 patients with adenocarcinoma in situ (AIS) (n = 8), minimally invasive adenocarcinoma (MIA) (n = 8), and invasive adenocarcinoma (IAC) (n = 14) were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 42 publications
7
108
2
Order By: Relevance
“…However, Castagnola et al also demonstrated that aneuploidy, global genomic derangement (measured as the total number of Copy Number Alterations, CNAs), and specific focal CNAs are present early in the evolution of oral cancer and are more frequent at later stages [73]. These results are in accordance with Zhang et al, who showed that, before the acquisition of invasion, immunoediting and intratumor genomic heterogeneity are early events that may happen [77]. Interestingly, Gu et al showed that, in the tumor-free tongue of patients with SCCOT, the cytolytic activity has clinical relevance rather than the levels of immune infiltration or degree of cytolytic activity within the tumor [78].…”
Section: Mutational Load and Immunology: Should These Factors Be Analsupporting
confidence: 56%
See 2 more Smart Citations
“…However, Castagnola et al also demonstrated that aneuploidy, global genomic derangement (measured as the total number of Copy Number Alterations, CNAs), and specific focal CNAs are present early in the evolution of oral cancer and are more frequent at later stages [73]. These results are in accordance with Zhang et al, who showed that, before the acquisition of invasion, immunoediting and intratumor genomic heterogeneity are early events that may happen [77]. Interestingly, Gu et al showed that, in the tumor-free tongue of patients with SCCOT, the cytolytic activity has clinical relevance rather than the levels of immune infiltration or degree of cytolytic activity within the tumor [78].…”
Section: Mutational Load and Immunology: Should These Factors Be Analsupporting
confidence: 56%
“…However, the vast increase in knowledge resulting from cancer research in recent decades made it possible to identify with greater accuracy the varying degrees of disparate genetic, molecular, transcriptomic, and immunologic profiles that characterize preneoplastic lesions. Some therapeutic strategies for the molecular cancer prevention are the use of natural or synthetic compounds that stop the prime drivers, key imbalances, or the context in which these drivers act and in which the derangements occur, prior to invasion across the basement membrane [11,77,106,107]. Among therapies targeting head and neck cancer, immunotherapy has gained attention in recent years, not only for treatments of advanced diseases but also as molecular prevention therapy [11,77,106,107].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results follow these findings suggesting that the localization of CD8 positive cells is more frequently found in the epithelium +/− the submucosa; whereas CD8 positive cells are only located in the submucosa when no medical history of squamous cell carcinoma was found. For atypical adenomatous hyperplasia, which is the pre-invasive counterpart of bronchial dysplasia for lung adenocarcinoma, it has recently been shown that tumors positive for both PD-L1 and CD8 had a larger proportion of subclonal mutations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 With the maturity of high-throughput technology and the development of many algorithms aimed at studying tumor immunity (single sample Gene Set Enrichment Analysis [ssGSEA], quanTIseq, CIBERSORT, etc), [17][18][19] it is possible to describe the landscape of tumor immune microenvironment (TME) through transcriptome sequencing. 20,21 However, no studies have systematically delineated the TME in BCa. We constructed an immune signature of 13-mRNA based on the least absolute shrinkage and selection operator (LASSO) algorithm and then, the TME landscape of BCa was depicted according to two currently popular algorithms and quantitatively estimated the main immune cells, thus finding a significant correlation between immune signature score (ISS) and immune escape phenotype.…”
Section: Introductionmentioning
confidence: 99%